Sustainable Place Making: Australian Exemplars - Christopher Wren (Fábos Conference on Landscape and Greenway Planning, 2010)
This paper provides the background to the case studies that will be presented at the conference. It is aimed at providing a concise view of what constitutes a sustainable place and the important subtleties in achieving an active, walkable and safe environment that is diverse, humane and attractive to people.
Keywords: greenways; placemaking; australia; urban; landscape; design; planning